Implementasi Sistem Hybrid Monitoring dan Penstabilan pH Air Tambak Udang Vaname Berbasis ESP32 dengan Metode Fuzzy Mamdani - Handinata, Achmad Cahya; Zuhriya Khoirunnisaa, Alfi (SURYA TEKNIKA, 2026)
Whiteleg shrimp (Litopenaeus vannamei) is a high-value export commodity that significantly impacts pond water quality, particularly pH and temperature parameters. Conventional pH management is considered slow and unresponsive to sudden changes. This study designed a hybrid system for monitoring and stabilizing pond water pH automatically using an ESP32 microcontroller with Mamdani fuzzy logic. The system integrates pH sensors, MAX6675 temperature sensors, and HC-SR04 ultrasonic sensors as inputs, as well as a drain pump and servo motor as actuators. The hybrid mode allows the system to operate offline or online through the Blynk platform. Test results showed an average error of 0.91% for the temperature and pH sensors, and 0.098% for the ultrasonic sensor. Fuzzy logic testing resulted in 100% agreement on 10 test data sets. This system is expected to improve the efficiency of water quality management and reduce the risk of shrimp mortality due to sudden pH changes.